Hierarchically-Ordered Zeolites: A Critical Assessment - Hartmann, Martin; Thommes, Matthias; Schwieger, Wilhelm (Advanced Materials Interfaces, 2021)
Hierarchically-ordered zeolites have received increasing attention in the last 15 years due to their outstanding properties, which are explored in catalytic reaction with industrial relevance. Up to now, a large number of different synthetic strategies have been reported that allow to introduce an additional meso- or macropore system in addition to the intrinsic microporosity of classical zeolites. Thus, hierarchical zeolites combine the intrinsic (catalytic) properties of conventional zeolites with facilitated access and transport via the additional pore system. In this critical review, the various synthesis pathways reported so far are evaluated, several physico-chemical methods required for in-depth characterization of the hierarchical pore system are discussed, and selective applications that are or potentially will be of technical relevance are introduced. The present review provides a critical analysis of the present achievements and discusses future opportunities and challenges for the research on hierarchically-ordered zeolite in particular with respect to their industrial use.
CRIS-Team Scopus Importer:2021-03-05
Keywords: advanced characterization; catalysis; hierarchically-ordered materials; porous materials; separation